Efeito do jejum intermitente associado ao treinamento aeróbico sobre a saúde e o desempenho físico de ratos wistar - Dorand, Victor Augusto Mathias (2023)
Intermittent fasting (IF) is characterized by the abstention from food intake, with the duration varying according to the protocol, with time-restricted feeding being one of the most popular protocols. The effects of this intervention are still controversial, with evidence of fat loss, but also potential deterioration in physical performance. Furthermore, most IF studies focus on the treatment or prevention of chronic diseases, meaning there is a lack of research on healthy individuals, whether or not combined with exercise. Considering these aspects, the objective was to evaluate parameters related to physical performance and health, such as body composition, metabolic parameters like lipid, glucose, and hormonal profiles, as well as inflammatory and oxidative parameters in Wistar rats subjected to IF, with or without aerobic training. A total of 40 healthy Wistar rats, approximately 140 days old, were used in the study and randomized into four groups: sedentary controls (SC) and trained (TC), and those subjected to sedentary fasting (SIF) and trained fasting (TIF). The SIF and TIF groups followed a time-restricted fasting protocol (15 hours fasting, 9 hours feeding) for 4 weeks. Simultaneously, the trained groups engaged in treadmill running 5 times a week, with each session lasting 30 minutes. Performance tests were conducted at the beginning and end of the exercise protocol. At the end of the experiment, somatic parameters, food consumption, muscular histology, as well as lipid profile, insulin, leptin, alpha-1-acid glycoprotein, C-reactive protein (CRP), markers of muscle damage, and oxidative markers were evaluated. The TIF group showed body weight loss (-16g ± 6.12g) and lower lean mass (22.49%), LDL (43%), HOMA-IR (29%), and LDH (48%), as well as higher MDA (53%) and CAT (75%) compared to TC group, which had body weight (10.63g ± 7.76g), lean mass (25.78 ± 1.51), LDL (18.86 ± 1.60), HOMA-IR (21.79 ± 1.97), LDH (5582 ± 756), MDA (3.70 ± 0.19), and CAT (14.98 ± 2.41). The TIF group also exhibited reduced glucose and insulin tolerance compared to CT. Alpha-1-acid glycoprotein and creatine kinase were similar among the groups, but the trained groups had lower CRP compared to controls. In the performance test, there was no difference between TC and TIF, and both groups showed significant improvement in performance at the end of the experiment. There was a decrease in sarcomere size with areas of tissue loss and inflammatory processes in the soleus and extensor digitorum longus muscles in JT and JS. These results demonstrate that IF combined with aerobic exercise yields negative outcomes in terms of body composition, muscle morphology, and oxidative markers, while not altering physical performance within the experimental timeframe.